2018
DOI: 10.4236/jcdsa.2018.83012
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Panel Size in Sensory Cosmetic Product Evaluation: A Pilot Study from a Statistical Point of View

Abstract: Subjective evaluations are nowadays applied more commonly in cosmetic product assessment. They are used in quality control, product development steps and efficacy studies for claim support. Several studies have been published to determine the adequate number of panelists, but recommendations and guidelines dealing with this topic are rare in the cosmetic sector. The aim of the present pilot study was to recommend a suitable study plan and define the adequate consumer panel size for cosmetic consumer assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Several studies have shown that skin cleansing and bathing products have the potential to improve mood, provide well-being and affect the human psychological state [42][43][44]. To generally evaluate emotions under cosmetic application the objective emotional assessment (OEA) was developed [45].…”
Section: Reducing Stress and Emotional Inconveniencementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that skin cleansing and bathing products have the potential to improve mood, provide well-being and affect the human psychological state [42][43][44]. To generally evaluate emotions under cosmetic application the objective emotional assessment (OEA) was developed [45].…”
Section: Reducing Stress and Emotional Inconveniencementioning
confidence: 99%
“…Whereas powerful 'instruments' such as OEA exist to evaluate the short-term effects of single cosmetic products on a single psychophysiological effect, like relaxation [43], activation [44] or stress reduction [42,46], up to now no superordinated study (or no adequate combination of 'instruments') has been published to evaluate long-term and holistic effects of skin cleansing on consumers quality of life and well-being. Therefore, an adequate combination of 'instruments' such as OEA and QoL assessments applied over a reasonable time period should be considered in future research on skin cleansing, bathing and shower procedures.…”
Section: Evaluation Of the Impact On Mood-and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, instruments can miss some subjective aspects despite the fact that they provide quantitative information and accurately measure product characteristics, so sensory studies should supplement rheology and texture analysis [ 21 ]. For this reason, subjective surveys of cosmetic products are standard practice because there is a critical need for direct consumer feedback [ 22 ]. Ideally, cosmetic products should perfectly meet the sensory expectations of consumers, who usually select a skin care product for its function and promising efficacy but are mostly seduced by the pleasantness it brings [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, cosmetic products should perfectly meet the sensory expectations of consumers, who usually select a skin care product for its function and promising efficacy but are mostly seduced by the pleasantness it brings [ 23 ]. In consumer sensory studies, the assessors evaluate the intensity of product attributes or the reaction of a particular body area [ 22 ]. The results of the assessment, correlating instrumental measurements, can be a very effective tool for predicting consumer responses.…”
Section: Introductionmentioning
confidence: 99%